(untitled) (SigMe, 2025)
The epilepsy affects more than 50 million people worldwide, and nearly 80% of them live in low- and middle-income countries (LMICs), where the estimated prevalence is around 10%. In these regions, the treatment gap is alarming: more than 75% of people do not receive adequate care. The Intersectoral Global Action Plan on Epilepsy and Other Neurological Disorders (IGAP) seeks / seek to improve access to care and treatment, promote brain health, and reduce the burden of these disorders. In Argentina, the Liga Argentina Contra la Epilepsia (LACE), in collaboration with the School of Medicine at Universidad Nacional del Litoral, conducted a monitoring initiative aimed at evaluating access to diagnostic methods and available treatments for healthcare professionals managing epilepsy. A descriptive, observational, and cross-sectional study was carried out. It consisted of 369 self-administered surveys: 218 neurologists, 100 pediatric neurologists, 30 pediatricians, 7 general practitioners or clinicians, and 14 professionals from other specialties. In terms of health care levels, 19.9% worked in primary care, 39.4% in secondary care, and 40.7% in tertiary care. Regarding the health system, 8.1% worked exclusively in the public sector, 43.3% in the private sector, and 48.6% in both sectors. The main barriers identified were professional training, medical coverage, access to specialists, and access to diagnostic tools. These findings provide a foundation for developing plans to improve timely diagnostic and treatment accessibility for epilepsy